“Busting the hidden curriculum” a realist and innovative perspective to foster professional behaviors - Guraya, Shaista Salman; Kearney, Grainne P.; Doyle, Frank; Sadeq, Asil; Bensaaud, Abdelsalam; Clarke, Eric; Harbinson, Mark; Ryan, Aine; Smyth, Mary; Hand, Sinead; Boland, Fiona; Guraya, Salman Yousuf; et al. (Frontiers in Medicine, 2024)
Contemporary health professions education has long delineated the desired attributes of medical professionalism in the form of standard curricula and their role in forming professional behaviors (PBs) among aspiring doctors. However, existing research has shown the contradictory and powerful role of hidden curriculum (HC) in negatively influencing medical students' PBs through unspoken or implicit academic, cultural, or social standards and practices. These contrasting messages of formal curricula and HC lead to discordance and incongruence in future healthcare professionals developing professional identity formation. There is little research on PB modifying educational strategies and their determinants that medical schools adopt to bust the impact of HC. Consequently, it is unclear how the right PBs can be influenced, entrenched, and inculcated in undergraduate medical students, especially in their early clinical placements. The lack of such insight highlights a critical gap in the literature, nudging educators to take a realist stance to deal with this problem. Behavior psychology stresses shaping medical students' values and beliefs as salient mediators that influence intentions to pursue future PBs. Curiosity prevails about what would guide the educational interventions to target this behavior change. To help understand this concept, we present our design-based innovative perspective about PROfessionalism in Partnership for Education Research (PROPER) shaped by pluralistic theoretical models in the context of two European medical schools with diverse medical students, highlighting its non-parochial and transferable nature.